Insulinoma camouflaged by vague neuroglycopenic symptoms: A case report - Mahapure, Kiran Sunil; Metgud, Shrishail Chandrakant (Indian Journal of Case Reports, 2020)
Pancreatic endocrine tumors are rare lesions, with a reported incidence of four cases per 1 million patients per year. Of them, insulinomas are the most common. These are usually benign, solitary, and small size (